Charlemagne, Muhammad, and the Arab roots of capitalism - Heck, Gene W. (Studien zur Geschichte und Kultur des islamischen Orients (2004), 2006)
Presented in six principal analytic chapters with supporting appendices, this book explores the role of Islam in precipitating Europe's twelfth century commercial renaissance. Employing the classic analytic techniques of economics, Gene Heck determines that medieval Europe's feudal interregnum was largely caused by indigenous governmental business regulation and not by shifts in international trade patterns. He then proceeds by demonstrating how Islamic economic precepts provided the ideological rationales that empowered medieval Europe to escape its three-centuries-long experiment in "Dark Ag